Coping with Toothache Pain: A Qualitative Study of Low-Income Persons and Minorities - Leonard A. Cohen, DDS, MPH, MS; Shelly L. Harris, MPH; Arthur J. Bonito, PhD; (Blackwell Synergy, 2007)
This study examined the behavioral impact of toothache pain as well as self-care strategies for pain relief among minority and low-income individuals.